Notes on the Akathiston at Arbore - Constanţa Costea (Revue Roumaine d'Histoire de l'Art : Série Beaux-Arts, 2010)
The disordered scenes of the Arbore Akathiston have been identified, resorting to parallel versions, in connection with the stanzas they illustrate; remarks on the infrequent arrangement of images lead to certain supposed new meanings of the cycle, revealing characteristics of the Moldavian society’s life towards the middle of the 16th century: prayer and pain.